Prolonged inhibition of intratumoral mast cells enhances efficacy of low-dose antiangiogenic therapy: molecular cancer biology - Berenbrok, Nikolaus; Vargas-Delgado, Maria Elena; Beitzen-Heineke, Antonia; Schmidt, Claudia; Gensch, Victoria; Loges, Sonja; Ben-Batalla, Isabel (International journal of cancer, 2025)
Low-dose antiangiogenic therapies have demonstrated the ability to enhance normalization of tumor vessels, consequently improving hypoxia levels, drug delivery, and promoting anticancer immune responses. Mast cells have been identified as contributors to resistance against antiangiogenic therapy and facilitators of abnormal neoangiogenesis. In this study, we demonstrate that by simultaneously targeting intratumoral mast cells with Imatinib and administering low-dose anti-VEGFR2 therapy, antitumor efficacy can be enhanced in preclinical models. Thus, combinatory treatment overcomes therapy resistance, while concurrently promoting tumor vessel normalization. Notably, histomorphometric analysis of tumor sections revealed that vessel perfusion could be improved through mast cell inhibition and, despite a significantly reduced microvessel density, the combination treatment did not result in elevated tumor hypoxia levels compared to anti-VEGFR2 therapy alone. Short-term Imatinib application effectively increased antitumor efficacy, and by prolonging the application of Imatinib tumor vessel normalization was additionally improved. The combination of mast cell depletion and antiangiogenic treatments has not been investigated in detail and promises to help overcoming therapy resistance. Further studies will be required to explore their impact on other treatment approaches, and subsequently to validate these findings in a clinical setting.
Zuerst veröffentlicht: 22. August 2024
Gesehen am 04.11.2024